If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x = -2(3x + -5) Reorder the terms: 4x = -2(-5 + 3x) 4x = (-5 * -2 + 3x * -2) 4x = (10 + -6x) Solving 4x = 10 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 4x + 6x = 10 + -6x + 6x Combine like terms: 4x + 6x = 10x 10x = 10 + -6x + 6x Combine like terms: -6x + 6x = 0 10x = 10 + 0 10x = 10 Divide each side by '10'. x = 1 Simplifying x = 1
| z^3-3iz^2-3z+i+1=0 | | 10m/5m | | -9x+12x-10-4x-2x=47 | | 0.3x+0.4=0.9x-1.4 | | 3x^2-8k=16 | | 2y-10x^2+4=0 | | 8+3m-3=9m+12-5m | | 4t-6=12t-24+18 | | 78+3x=10x-97 | | 6/z-3/z=15 | | 2(2x-3)=4(2x+2) | | 12-x/2=x/5 | | 2x-5/12-3x/6=11/12 | | 4x^2-2x+30=0 | | 5x+35=86 | | 13=3(x-4)-(x-9) | | 76+6x=-11x-145 | | G(x)=2x+1 | | 0.5x+1.9=0.8x-0.2 | | (4x-9z)(3x+5z)= | | 7x-20=33 | | (x^6y^-3/z^-1)-5 | | 0.19x+0.2(x-4)=0.01(5x-2) | | kx^2+k=8x-2xk | | 4(x-3)+1=6x-2(4+x) | | 1.67u-1.67=1.25-.67 | | 1.5x=x+15 | | 0.12(y-7)+0.18y=0.10y-0.6 | | .9y-3.6=-.3y+3 | | 7x-7=8+6x | | 3(4y+4)=10 | | 28x+35=8x-27 |